Analysis of the Survey on Coaching of Athletes with Disabilities in Volleyball at NPC Indonesia: Analisis Survei Pembinaan Atlet Disabilitas Cabang Olahraga Bolavoli Duduk di NPC Indonesia - Ismail, Taufik; Sugiyanto; Purnama, Sapta Kunta (Procedia of Social Sciences and Humanities, 2022)
The purpose of this study was to find out 1) The existence of coaching athletes with disabilities in the Indonesian national volleyball division, 2) Human resources in coaching athletes with disabilities in the Indonesian national team for athletes with disabilities, 3) Availability of training facilities and infrastructure for athletes with disabilities in soccer. sitting volleyball. This research was conducted at the Indonesian NPC in Surakarta. The method used is qualitative with an interpretive basic study approach. Data collection techniques used are document and archive studies, in-depth interviews, observation. The validity of the data in this study used data triangulation techniques. Data analysis techniques are data reduction, data presentation, conclusion drawing and verification. The results showed that the development of athletes with disabilities in the volleyball sport of the Indonesian National Team in Surakarta could be said to be good. Judging from the availability of human resources consisting of sports coordinators, coaches and athletes who are fostered through 2 recruitment programs by looking at the quality and quantity of prospective athletes and coaches, as well as by showing their certificates. The availability of infrastructure in the form of an Indonesian sitting volleyball hermitage and a fitness laboratory located in the fitness center of the Alana hotel on the 2nd floor. The conclusion is that the implementation of training for athletes with disabilities in Indonesian volleyball in Surakarta is maximal. Judging from the existence, human resources, availability of infrastructure. Although there are still some things that need to be improved again to achieve the vision and mission of coaching athletes with disabilities in volleyball at the Indonesian National Championship.